Pengaruh Pemberian Buah Kurma Terhadap Peningkatan Kadar Hemoglobin Ibu Hamil - Zuriyanisyah Rauf; Fidyawati Aprianti A Hiola; Yuliandary Yunus; Levana Sondakh (ProHealth Journal, 2026)
Low hemoglobin levels in pregnant women are a common health problem and can increase the risk of pregnancy complications, preterm delivery, and maternal-infant mortality. This condition is mostly caused by iron deficiency. Although the government has implemented efforts to distribute Iron-Folic Acid tablets (TTD) to prevent anemia, some pregnant women have not adhered. Contributing factors include poor adherence to TTD consumption, and side effects experienced by some pregnant women. This indicates the need for administration of dietary alternatives. One such alternative is date fruit consumption, which contains iron and antioxidants that may help increase hemoglobin levels. This study aimed to determine the effect of date fruit consumption on hemoglobin levels among pregnant women in the work area of the Talaga community health center. The study employed a two-group pretest-posttest design, consisting of an intervention group and a control group. The results showed a significant difference in hemoglobin levels. The intervention group increased from 10.13 g/dL to 11.18 g/dL, while the control group increased from 10.27 g/dL to 10.29 g/dL. Statistical analysis revealed that the difference in hemoglobin levels in pregnant women who consumed dates was significant with a p-value < 0.05. In conclusion, seven days consumption of dates can serve as an effective nutritional supplement for preventing and managing anemia during pregnancy.